An investigation into the effects of pulp chemistry under wet and dry grinding on the flotation response of pyrite - Tseka, Relebohile (Department of Chemical Engineering, 2019)
Considering the depletion of high-grade ore deposits, the mining industry is faced with the challenge of processing low grade and more complex ores in order to meet the growing demand for metals and metal products. Therefore, it is of paramount importance to have a fundamental understanding of minerals processing operations in order to improve the recoveries of valuable metals on an industrial scale. It has been acknowledged that the chemical conditions during grinding as well as pulp chemistry have a significant influence on the recovery and selectivity of most sulphide minerals in the flotation process. Floatability of ores is mostly determined by surface properties and the surface properties are essentially controlled by the grinding conditions. The flotation response of sulphide minerals is influenced by factors such as: collector-mineral interactions, mineral surface oxidation, deposition of iron hydroxides/oxides from grinding media and the attachment of inorganic ions on the surfaces of minerals. These factors are on the other hand affected by dissolved oxygen (DO), pH, ionic strength of process water and other pulp chemistry factors. With the highly instrumented Magotteaux Mill® , the effects of these variables may be investigated during grinding. Several studies have shown that the grinding environment plays a vital role in the selectivity and recovery of sulphide minerals. During wet grinding, water allows the flow of electrons within the pulp (galvanic interactions between minerals themselves and minerals and grinding media). Pyrite is reactive and can easily oxidise when exposed to air or oxygen. Pyrite and most sulphide minerals are more inert than the electrochemically reactive grinding media. Therefore, during grinding, grinding media come into frequent contact with sulphide minerals and a galvanic couple is created between the grinding media and sulphides. Due to galvanic interactions, oxygen reduction occurs on the sulphide mineral surface and iron oxidation takes place on the steel media. The redox reaction results in the formation of iron oxy-hydroxides on the surface of sulphide minerals. The oxy-hydroxide species prevent the adsorption of collector onto the mineral surface, making the mineral less floatable. Dry grinding limits the galvanic interactions present during wet grinding, due to the absence of water. Studies have been conducted and it has been shown that dry grinding yielded significantly less media wear relative to wet grinding owing to the absence of corrosive abrasion in the form of electrochemical oxidation of media during grinding. Reduced grinding media wear may imply that lesser iron hydroxide precipitates build up on the surface of the mineral hence improving collector adsorption and subsequently mineral recovery. Therefore, this suggests that dry grinding could result in improved sulphide mineral recovery as compared to wet grinding. It is necessary to consider the fundamental aspects of both grinding and flotation in order to improve concentrator performance as well as sulphide mineral recovery in the presence of nonsulphide minerals. Previous studies have investigated the influence of the grinding pulp chemistry factors on the flotation response of pyrite and other pure sulphide minerals. The possible influence that the presence of a non-sulphide gangue mineral may have during grinding and flotation has been ignored. The non-sulphide gangue cleans the surface of the sulphide minerals. Studies have shown that presence of quartz influences the formation of layers of hydrophilic species on the surface of sulphide minerals. The metal hydroxides will preferably deposit on the surface of non-sulphide mineral such as quartz rather than sulphide minerals. These studies also did not investigate the combined effects of pulp chemistry factors under dry and wet grinding. It should be noted that it is not possible to control pulp chemistry during dry grinding, thus these variables are controlled in the flotation cell in order to understand their effect on mineral surface after dry milling on pyrite flotation recovery relative to how they change the minerals surface properties during grinding. Change in chemical, surface properties of sulphide minerals can take place during milling and froth flotation. Therefore, this study aims to investigate the effects of DO, pH and grinding media type (forged steel and ceramic media) during milling and flotation process on the flotation response of pyrite (sulphide mineral) in the presence of quartz (non-sulphide gangue material). Wet milling was conducted in a Magotteaux Mill® while a Sala Batch grinding mill was used to carry out dry grinding. DO concentration and pH were controlled and measured in situ during wet grinding and were manipulated inside the flotation cell after dry grinding. The effects of the DO and pH, with changing grinding media type, on water and solids recovery, pyrite recovery and grade as well as flotation kinetic constants were studied. The EDTA extraction technique was employed to quantify the percentage of extractable oxidized iron leached from the mill product. The findings of this study have shown that under both wet grinding and dry grinding, an increase in pH from 9 to 11 resulted in increased water and solids recovery due to an increase the total concentration of OH ions in the system which led to increased froth stability owing to the reduction in pulp bubble size, as well as reduced bubble coalescence. This shows that the control of pulp chemistry during milling and flotation affected flotation process in the same way. The study has further shown that the highest recovery of pyrite, 100%, was achieved with inert grinding media (ceramic) under dry grinding. This might be due to cleaner pyrite surfaces created during dry grinding, since the prevention of media corrosion may lead to improved recoveries. During wet grinding, iron hydroxide is generated and reduces the flotation response of pyrite. Dry grinding generally produces much faster pyrite flotation kinetics than wet grinding because of the generation of particles with high surface energy and that leads to highly activated particles. It was therefore concluded that the grinding environment indeed has an effect on the flotation response of pyrite in the presence of gangue. This study has shown that careful manipulation of pulp chemistry, selection of grinding media and grinding environment may be used to manage pyrite recoveries within flotation.